Increased lipogenesis in spite of upregulated hepatic 5'AMP‐activated protein kinase in human non‐alcoholic fatty liver. Issue 9 (18th November 2016) - von Loeffelholz, Christian; Döcke, Stephanie; Lock, Johan F.; Lieske, Stefanie; Horn, Paul; Kriebel, Jennifer; Wahl, Simone; Singmann, Paula; de las Heras Gala, Tonia; Grallert, Harald; Raschzok, Nathaniel; Sauer, Igor M.; et al.
Abstract : Aims: Molecular adaptations in human non‐alcoholic fatty liver disease (NAFLD) are incompletely understood. This study investigated the main gene categories related to hepatic de novo lipogenesis and lipid oxidation capacity. Methods: Liver specimens of 48 subjects were histologically classified according to steatosis severity. In‐depth analyses were undertaken using real‐time polymerase chain reaction, immunoblotting, and immunohistochemistry. Lipid profiles were analyzed by gas chromatography/flame ionization detection, and effects of key fatty acids were studied in primary human hepatocytes. Results: Real‐time polymerase chain reaction, immunoblotting, and immunohistochemistry indicated 5'AMP‐activated protein kinase (AMPK) to be increased with steatosis score ≥ 2 (all P  < 0.05), including various markers of de novo lipogenesis and lipid degradation (all P  < 0.05). Regarding endoplasmic reticulum stress, X‐Box binding protein‐1 (XBP1) was upregulated in steatosis score ≥ 2 ( P  = 0.029) and correlated with plasma palmitate ( r  = 0.34; P  = 0.035). Palmitate incubation of primary human hepatocytes increased XBP1 and downstream stearoyl CoA desaturase‐1 mRNA expression (both P  < 0.05). Moreover, plasma and liver tissue exposed a NAFLD‐related lipid profile with reduced polyunsaturated/saturated fatty acid ratio, increased palmitate and palmitoleate, and elevated lipogenesis and desaturation indices with steatosis score ≥ 2 (all P  < 0.05). Conclusion: In humans with advanced fatty liver disease, hepatic AMPK protein is upregulated, potentially in a compensatory manner. Moreover, pathways of lipid synthesis and degradation are co‐activated in subjects with advanced steatosis. Palmitate may drive lipogenesis by activating XBP1‐mediated endoplasmic reticulum stress and represent a target for future dietary or pharmacological intervention.